Carboxylated, Fe‐Filled Multiwalled Carbon Nanotubes as Versatile Catalysts for O2 Reduction and H2 Evolution Reactions at Physiological pH. Issue 36 (14th July 2015) - Bracamonte , M. Victoria; Melchionna, Michele; Stopin, Antoine; Giulani, Angela; Tavagnacco, Claudio; Garcia, Yann; Fornasiero , Paolo; Bonifazi , Davide; Prato, Maurizio
Abstract The development of new electrocatalysts for the oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER) at physiological pH is critical for several fields, including fuel cells and biological applications. Herein, the assembly of an electrode based on carboxyl‐functionalised hydrophilic multiwalled carbon nanotubes (MWCNTs) filled with Fe phases and their excellent performance as electrocatalysts for ORR and HER at physiological pH are reported. The encapsulated Fe dramatically enhances the catalytic activity, and the graphitic shells play a double role of efficiently mediating the electron transfer to O2 and H2O reactants and providing a cocoon that prevents uncontrolled Fe oxidation or leaching.